2020
DOI: 10.22437/bio.v6i1.8458
|View full text |Cite
|
Sign up to set email alerts
|

Manual Book Biology Scientific Camp: Pengembangan Pendidikan Karakter Berbasis Outdoor Approach

Abstract: This research aimed to develop a manual book for the implementation of a biology scientific camp to develop the character education of biology students. This book was developed with an outdoor approach. This research uses the ADDIE development model which includes the Analysis, Define, Design, Implementation and Evaluation. This research data were obtained from the results of the validation of material experts and media experts as well as the results of small group trials. The results showed the results of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
1
0
3
Order By: Relevance
“…Untuk itu pendidik harus membuat rencana pembelajaran termasuk pengalaman belajar peserta didik yang membuat sikap peserta didik terhadap mata pelajaran menjadi lebih positif. Penggunaan media pembelajaran oleh pendidik dalam proses belajar mengajar dapat memberi pengaruh positif pada sikap siswa dan meningkatkan motivasi belajar siswa (Hakim et al, 2020).…”
Section: Sikap Belajarunclassified
“…Untuk itu pendidik harus membuat rencana pembelajaran termasuk pengalaman belajar peserta didik yang membuat sikap peserta didik terhadap mata pelajaran menjadi lebih positif. Penggunaan media pembelajaran oleh pendidik dalam proses belajar mengajar dapat memberi pengaruh positif pada sikap siswa dan meningkatkan motivasi belajar siswa (Hakim et al, 2020).…”
Section: Sikap Belajarunclassified
“…Penggunaan media pembelajaran oleh pendidik dalam proses belajar mengajar dapat memberi pengaruh positif pada siswa dan meningkatkan motivasi belajar siswa (Hakim et al, 2020). Video termasuk salah satu media pembelajaran audio visual, yang tidak hanya menyajikan gambar, namun juga suara secara bersamaan dan berada dalam satu unit (Lukman et al, 2019).…”
Section: Pendahuluanunclassified
“…Over the past few years, there have been several empirical studies that have examined the use of technology in the distance learning process and views of students' responses in the learning process. But many of those studies consistently found that teachers have to struggle to understand the learning activities and they need to hold skills to organize the learning process and students' participation in the learning activities (Zulhelmi, et al, 2017;Antika & Haikal, 2019;Adarkwah, 2020;Babinčáková & Bernard, 2020;Hakim, et al, 2020). All researchers mentioned that media can also be an alternative for teachers in providing variations in the teaching and learning process, attracting students' attention, and gaining students understanding of the content material (Muhson, 2010;Panjaitan, et al, 2016;Salyani, et al, 2018;Panjaitan, et al, 2019;Wulandari, et al, 2020;Sari & Harahap, 2021 ).…”
Section: Introductionmentioning
confidence: 99%